2016
DOI: 10.1080/09687688.2017.1400602
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial outer membrane vesicles: New insights and applications

Abstract: Outer membrane vesicles (OMVs) (∼50-250 nm in diameter) are produced by both pathogenic and nonpathogenic bacteria as a canonical end product of secretion. In this review, we focus on the OMVs produced by gram-negative bacteria. We provide an overview of the OMV structure, various factors regulating their production, and their role in modulating host immune response using a few representative examples. In light of the importance of the diverse cargoes carried by OMVs, we discuss the different modes of their en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 118 publications
(174 reference statements)
1
44
0
1
Order By: Relevance
“…The strength of lipopolysaccharide bilayers can evidently be modulated through LPS capping/Oantigen expression, providing a simple method to control the durability of outer membrane vesicles, which are increasingly being used as vaccine adjuvants and are garnering attention for their potential nanomedicinal applications. [54][55][56] Modulating the mechanical strength of comparable glycerophospholipid nanocarriers through the incorporation of amphiphilic block copolymers was shown to not only enhance their shelf stability but also to reduce their toxicity, and increase the loading rates of drugs and drug cellular uptake. [57][58][59] Going forward, the use of alternative simulation methods that can…”
Section: Resultsmentioning
confidence: 99%
“…The strength of lipopolysaccharide bilayers can evidently be modulated through LPS capping/Oantigen expression, providing a simple method to control the durability of outer membrane vesicles, which are increasingly being used as vaccine adjuvants and are garnering attention for their potential nanomedicinal applications. [54][55][56] Modulating the mechanical strength of comparable glycerophospholipid nanocarriers through the incorporation of amphiphilic block copolymers was shown to not only enhance their shelf stability but also to reduce their toxicity, and increase the loading rates of drugs and drug cellular uptake. [57][58][59] Going forward, the use of alternative simulation methods that can…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, LPS and other bacterial antigens may exert profound neurotoxic effects [28] by accessing the brain via different routes, including the blood-brain-barrier, the circumventricular organs and area postrema, or via outer membrane vesicles [28][29][30][31][32][33]. Based on this knowledge, we concluded that schizophrenia patients with lowered natural IgM are more prone to the detrimental effects of LPS and other bacterial neurotoxic antigens, which in turn may drive schizophrenia symptoms including memory impairments [25].…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the observed surface structures on cells of strain LFY10 were membrane vesicles (MVs). The production of MVs is widespread among microorganisms, discovered first in Gram-negative bacteria and since identified in species from all three domains of life (Deatherage and Cookson, 2012; Anand and Chaudhuri, 2016). Pseudomonas fluorescens , a close relative to strain LFY10, produces MVs that are formed when the outer membrane of the cell wall bulges outward, fills with periplasm, and then pinches off to form a spherical vesicle (Guyard-Nicodème et al, 2007; Anand and Chaudhuri, 2016), a process that is consistent with our observations of strain LFY10.…”
Section: Discussionmentioning
confidence: 99%